Efektivitas Model Problem Based Learning dalam Meningkatkan Kemampuan Literasi Numerasi Siswa Kelas 3 Sekolah Dasar - Erma Susanti; Dina Liana; Muhammadiyah, Muhammadiyah (Universitas 45 Surabaya, 2025)
Problem Based Learning (PBL) is an innovative instructional model designed to enhance students' numeracy literacy through real-world problem-solving. This study aims to evaluate the effectiveness of PBL in mathematics education for third-grade elementary students. Synthesizing previous research findings, it was revealed that PBL significantly contributes to improving students' cognitive skills, learning motivation, and self-efficacy. Factors such as technology integration, teacher-student relationships, and adapting instructional methods to students' needs were key to successful PBL implementation. Moreover, PBL aids students in understanding the relevance of mathematical concepts in daily life, strengthens analytical abilities, and fosters collaborative skills. This study underscores that PBL is a relevant approach to addressing challenges in mathematics education, including gender disparities and socio-economic differences. Therefore, PBL is recommended as an effective strategy to enhance the quality of elementary mathematics education.